Tissue-specific bioconcentration and biotransformation of cypermethrin and chlorpyrifos in a native fish (Jenynsia multidentata) exposed to these insecticides singly and in mixtures - Bonansea, Rocio Ines (2016)
The aim of the present study was to evaluate the accumulation of cypermethrin and chlorpyrifos when the fish Jenynsia multidentata was exposed to these pesticides singly and in technical and commercial mixtures. Adult female fish were exposed over 96 h to 0.04 μg/L of cypermethrin; 0.4 μg/L of chlorpyrifos; 0.04 μg/L of cypermethrin + 0.4 μg/L of chlorpyrifos in a technical mixture; and 0.04 μg/L of cypermethrin + 0.4 μg/L of chlorpyrifos in a mixture of commercial products. Fish exposed to cypermethrin accumulated this compound only in muscle, probably because of the low biotransformation capacity of this organ and the induction of cytochrome P4501A1 (CYP1A1) expression in the liver. The accumulation of chlorpyrifos occurred in fish exposed to the insecticide (intestine > liver > gills) even when these fish had higher gluthatione-S-transferase (GST) activin gills and P-glycoprotein (P-gp) expression in the liver, compared with the control. Fish exposed to the technical mixture showed cypermethrin accumulation (liver > intestine > gills) with higher levels than those measured in fish after only cypermethrin exposure. Higher expression levels of CYP1A1 in the liver were also observed compared with the Control. Fish exposed to the commercial mixture accumulated both insecticides (cypermethrin: intestine > gills and chlorpyrifos: liver > intestine > gills > muscle). In the organs where accumulation occurred, biotransformation enzymes were inhibited. Consequently, the commercial formulation exposure provoked the highest accumulation of cypermethrin and chlorpyrifos in J. multidentata, possibly associated with the biotransformation system inhibition.